Strategy, value and risk : a guide to advanced financial management - Rogers, Jamie (Palgrave Macmillan, 2013)
"Strategy, Value and Risk: A Guide to Advanced Financial Management examines this issue within the context of innovation, the evolution of industry sectors, and financial analysis, corporate finance, quantitative finance and risk management concepts. The short-term is addressed within the context of financial statement analysis and forecasts, stocks and flows, and ROCE and ROIC ratios. The long-term is examined using investment analysis techniques that include advanced accounting, DCF, ENPV and real options, a corporate finance concept that applies financial options theory to real assets using quantitative and derivative methods. These techniques are applied to real assets within the context of strategy in case studies that cover corporate IT, energy, pharmaceutical drug development, climate-change and growth, media and abandonment, and commercial real estate to illustrate the concepts and issues. This 3rd Edition features new strategy and analysis of performance sections, and updated introduction, value, risk and case study sections, that together provides a framework to examine the interrelationships between strategy, value and risk."--Resumé vydavatele
Keywords: finance podniku; finanční management; finanční investování; finanční rizika; opce (finance); finanční deriváty; business finance; financial management; financial investments; financial risks; options (finance); derivative securities; příručky; elektronické knihy; handbooks and manuals; electronic books